Evaluation of intake charge hydrogen enrichment in a heavy-duty diesel engine. (January 2018) - Monemian, Emad; Cairns, Alasdair; Gilmore, Mark; Newman, David; Scott, Keith
Concerns over CO2 emissions and global warming continue to enforce the transport sector to reduce the fuel consumption of heavy duty diesel goods vehicles as one of the major contributors of CO2 . Such powertrain platforms look set to remain the dominant source of heavy duty vehicle propulsion for decades to come. The currently reported work was concerned with experimental evaluation of the potential to partially displace diesel with hydrogen fuel, which continues to attract attention as a potential longer term alternative fuel solution, whether produced on-board or remotely via sustainable methods. The single cylinder engine adopted was of 2.0 litre capacity, with common rail diesel fuel injection and exhaust gas recirculation (EGR) typical of current production technology. The work involved fumigation of H2 into the engine intake system at engine loads typically visited under real world driving conditions. Highest practical hydrogen substitution ratios increased indicated efficiency by up to 4.6% at 6 bar net indicated mean effective pressure (IMEPn) and 2.4% at 12 bar IMEPn. In 6bar IMEPn, CO2, CO and soot all reduced by 58%, 83% and 58% respectively while the corresponding reduction of these emissions in 12 bar IMEPn, were 27%, 45% and 71% respectively toward diesel-only baseline. Under such conditions the use of a pre-injection prior to the main diesel injection was essential to control the heat release and pressure rise rates.